2013
DOI: 10.1016/j.colsurfb.2012.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Cell interaction study method using novel 3D silica nanoneedle gradient arrays

Abstract: Understanding cellular interactions with culture substrate features is important to advance cell biology and regenerative medicine. When surface topographical features are considerably larger in vertical dimension and are spaced at least one cell dimension apart, the features act as 3D physical barriers that can guide cell adhesion, thereby altering cell behavior. In the present study, we investigated competitive interactions of cells with neighboring cells and matrix using a novel nanoneedle gradient array. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The surface features (e.g. topography, compliance, texture) of the materials can impact the ability of NIH 3 T3 fibroblast cells to sense physical and chemical signals . In this study, the surface of BC was modified using the TEMPO‐mediated oxidation system.…”
Section: Introductionmentioning
confidence: 99%
“…The surface features (e.g. topography, compliance, texture) of the materials can impact the ability of NIH 3 T3 fibroblast cells to sense physical and chemical signals . In this study, the surface of BC was modified using the TEMPO‐mediated oxidation system.…”
Section: Introductionmentioning
confidence: 99%
“…This flexible technique is capable of producing user-defined patterns with nanometer resolution (13). In addition, we demonstrated that peptide-loaded nanopore substrates were stable enough to be shipped and stored at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…NIL has been applied to a wide of range of cell types. Key examples of such applications include fibroblasts, [ 111,112 ] osteoblasts, [ 113 ] neurons, [ 114–116 ] and mesenchymal stem cells (MSCs). [ 117 ] It is worthwhile mentioning that there are many important nonlithographic micropatterning methods such as microfluidic patterning, laminar flow patterning, stencil patterning, and emulsion freeze‐drying.…”
Section: Engineered Microsystems For Spheroids and Organoid Culturementioning
confidence: 99%